2002
DOI: 10.1002/app.10913
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dicarboxylates nucleation of β‐polypropylene

Abstract: Seven dicarboxylates of calcium were synthesized. The effect of dicarboxylate on the formation of ␤-form polypropylene was investigated by X-ray diffraction. Calcium pimelate, calcium suberate, calcium phthalate, and calcium terephthalate have been found to be an effective ␤-nucleator.The K x values of the isotatic propylene samples with 0.5 wt % of the nucleators above are 0.95, 0.96, 0.93, and 0.62, respectively. Calcium succinate, calcium adipate, and calcium sebacate behave invalidly on the nucleating of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 32 publications
3
51
0
Order By: Relevance
“…it is 137 cm -1 . This difference in the IR spectra of barium and strontium pimelate is 155 cm -1 (taking the frequency of the stretching symmetric COO mode as 1395 cm -1 ) and is close to the values found in the spectra of calcium pimelate (Δν = 160 [58]) and magnesium pimelate. On the other hand, in the structure of barium and strontium pimelates [42][43][44] it was found that the coordination mode of carboxylate groups is bridging tridentate.…”
Section: Fig 1 Infrared Spectra Of the Synthesized Pimelatessupporting
confidence: 80%
See 2 more Smart Citations
“…it is 137 cm -1 . This difference in the IR spectra of barium and strontium pimelate is 155 cm -1 (taking the frequency of the stretching symmetric COO mode as 1395 cm -1 ) and is close to the values found in the spectra of calcium pimelate (Δν = 160 [58]) and magnesium pimelate. On the other hand, in the structure of barium and strontium pimelates [42][43][44] it was found that the coordination mode of carboxylate groups is bridging tridentate.…”
Section: Fig 1 Infrared Spectra Of the Synthesized Pimelatessupporting
confidence: 80%
“…7), which is in accordance with literature data [25,58,29]. We have tried to evaluate the nucleation activity by determination of the content of the β-phase in the crystal phase of iPP since U β , in certain conditions, depends only on the character of the nucleating agent.…”
Section: Crystallization Of Nucleated Polymer and Correlation To The supporting
confidence: 75%
See 1 more Smart Citation
“…The modification of iPP ranges from the addition of rubbers, [1][2][3][4][5] thermoplastic elstomers, [6][7][8][9][10][11][12][13] rigid inorganic and organic fillers, 4,14 b-nucleating agent 15,16 to introduction of comonomers 17,18 and polymerization of in-reactor iPP catalloy, 19,20 etc. The well-known rubbery iPP modifiers included EPR, EPDM, SEBS, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…8 The preparation of 100% pure b-hexagonal phase polymer is reported by Li et al 9 In the unit cell of hexagonal phase, the helices are located in alternative rows with opposite direction and they possess the same sense of rotation. The axial repeat distance of hexagonal phase is found to be slightly less (c ¼ 0.635 nm) 5 than that found in the monoclinic cell (c ¼ 0.650 nm).…”
Section: Introductionmentioning
confidence: 96%